Pressure cell for investigations of solid-liquid interfaces by neutron reflectivity - Kreuzer, Martin; Kaltofen, Thomas; Steitz, Roland; Zehnder, Beat H.; Dahint, Reiner (Review of scientific instruments, 2011)
We describe an apparatus for measuring scattering length density and structure of molecular layers at planar solid-liquid interfaces under high hydrostatic pressure conditions. The device is designed for in situ characterizations utilizing neutron reflectometry in the pressure range 0.1-100 MPa at temperatures between 5 and 60 °C. The pressure cell is constructed such that stratified molecular layers on crystalline substrates of silicon, quartz, or sapphire with a surface area of 28 cm2 can be investigated against noncorrosive liquid phases. The large substrate surface area enables reflectivity to be measured down to 10−5 (without background correction) and thus facilitates determination of the scattering length density profile across the interface as a function of applied load. Our current interest is on the stability of oligolamellar lipid coatings on silicon surfaces against aqueous phases as a function of applied hydrostatic pressure and temperature but the device can also be employed to probe the structure of any other solid-liquid interface.